Ethical Governance of eGovernment Ecosystems - Jani Koskinen; Mikko Vermanen; Minna M. Rantanen; Sami Hyrynsalmi (Slovenia, 2022)
Digitisation of governmental services has become a common approach to make governing more effective and efficient. The eGovernment services can be built on top of a variety of information systems and supplied to and between individuals and organisations on both national and international levels. This results in a complex organisational and socio-technical ecosystem containing a vast amount of variables affecting the privacy and safety of citizens.Thus, achieving these better societies relies strongly on common trust between the citizens and governments. This calls for ‘governance of governance’, which can prove to be difficult to manage. Even in this challenging environment, it is crucial that ethical principles are applied to the highest possible degree. Yet, in current research, the citizens are often neglected.In order to develop a better society for all, we should objectively consider the ends and means of eGovernment. In this paper, we study the relation of the citizens and eGovernment systems from an ethical perspective in order to represent which ethical considerations should be made if one wishes to truly aim for a better society.
33rd Bled eConference Enabling Technology for a Sustainable Society: Conference Proceedings